Tajdīd Fiqh al-Marʻah al-Muslimah - Ely Maliki (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2006)
The renewal is one of debated discourse. That problem is contrast from Ulama perspective about the possibility of ijtihad. Fikih is an important part of a blown renewal agenda. This paper described the important of Fikih renewal in the mainstream gender.